1998
DOI: 10.1007/bf02765225
|View full text |Cite
|
Sign up to set email alerts
|

The role of vole populations in prevalence of the parasite (Echinococcus multilocularis) in foxes

Abstract: Abstract. Effects of population fluctuation of the gray-sided vole (Clethrionomys rufocanus) on the prevalence (infection rates) of the parasite Echinococcus multilocularis in red fox (Vulpes vulpes)populations was investigated from 1985 to 1992 in eastern Hokkaido (Abashiri, Nemuro, and Kushiro area), Japan. This parasite needs two hosts to complete its life cycle; the gray-sided vole as its intermediate host and the red fox as its final host. We found that: (1) Infection rates in foxes depended on the curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…A difference in the prevalence rate between Nemuro and Abashiri was also indicated by the field data (Table 1; Saitoh and Takahashi, 1998); the simulation showed that this was caused by a difference in snowfall between the two provinces.…”
Section: Discussionsupporting
confidence: 52%
“…A difference in the prevalence rate between Nemuro and Abashiri was also indicated by the field data (Table 1; Saitoh and Takahashi, 1998); the simulation showed that this was caused by a difference in snowfall between the two provinces.…”
Section: Discussionsupporting
confidence: 52%
“…An early major contribution to the transmission ecology of E. multilocularis between small mammals and foxes was given by Saitoh and Takahashi (1998). They investigated E. multilocularis winter prevalence dynamics in a sample of 9828 foxes (V. vulpes) and Myodes rufocanus population variations in three localities of Hokkaido, the northernmost island of Japan, over 8 years.…”
Section: E Multilocularis Transmission In Foxesmentioning
confidence: 99%
“…The existence of at least two density-dependent mechanisms acting on the control of the parasite transmission dynamics is described: one is based on the variations in the availability of resources including intermediate hosts (Rausch, 1995;Saitoh and Takahashi, 1998;Miterpakova et al, 2006;Tanner et al, 2006;Hegglin et al, 2007;Guislain et al, 2008;Robardet et al, 2008;Raoul et al, 2010;Stien et al, 2010;Wang et al, 2010;Liccioli et al, 2014), and the other is based on the variations in the density of the definitive host and in their faeces distribution (Ewald, 1993;Raoul et al, 2003;Guislain et al, 2007;Wang et al, 2010). However, we are clearly missing data to predict under which conditions the control of E. multilocularis transmission switches from being dominated by intermediate host density to being dominated by definitive host density, and vice-versa, in space and/or in time.…”
Section: Synthesis and Perspectivesmentioning
confidence: 99%
See 1 more Smart Citation
“…et al 1998). Saitoh and Takahashi (1998) demonstrated a close relation between C. rufocanus and foxes through the infection rate of the parasite Echinococcus multilocularis in the field.…”
Section: What Do We Know?mentioning
confidence: 88%